Aplikasi Virtual Gallery Berbasiskan Content Management System pada Jurusan Sistem Informasi Universitas Bina Nusantara - Vina Georgiana (ComTech: Computer, Mathematics and Engineering Applications, 2011)
A study program which represents a college will always attempt to link its activities with the needs of society and industry as for its graduates to be recognized outside. Various activities such as internships, industry reviews, theses, and others the need to show the results individually and be exposed widely, so that it becomes part of student testimonials at work. Displaying and publishing the work of academic community can be done with the support of information technology through a web-based application, called virtual gallery application, based on a content-management-system. The research object is limited on work of student activities on a study program. The base to manage and publish the work of academic community uses: (1) object-oriented method (2) web-based application development. Theevaluation results make easy the management of the academic community’s work, increase the competitive advantage of the graduates, and be able to improve the quality of a study program at a college.